Caracterização da radioatividade das águas do aquífero Guarani - Bueno, Thaís de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
This research aimed to evaluate the quality of “Aquifer Guarani’s” waters in the context of the current legislation related to the radioactive aspects, besides correlating the values obtained with chemical data already available, seeking to make an integrated analysis of the data in order to establish possible tendencies with directions of underground flow. The determinations of the total radioactivity beta and alpha were accomplished through the employment of the available infrastructure at the LABIDRO – Laboratory of Isotope and Hydrochemistry of the Petrology and Metallogeny of UNESP’s Institute of Geosciences and Exact Sciences, largely implanted through resources supplied by FAPESP and CNPq. The systems were gauged for the determinations of interest with tracer of known activity. Preliminaries tests were accomplished with high radioactivity samples of water to check the applicability of the methods. It was ended that the waters analyzed possess low radioactivity, as much alpha as total beta, and, therefore, they are appropriate for the human consumption; that there is not lineal relationship between the obtained data and the chemical data already available; and that the direction of the underground flow of the Aquifer doesn't check any tendency to the generated data.

Este trabalho objetivou avaliar a qualidade das águas do Aqüífero Guarani no contexto da legislação brasileira vigente quanto aos aspectos radiológicos, além de correlacionar os valores obtidos com dados químicos já disponíveis, visando efetuar uma análise integrada dos dados e estabelecer possíveis tendências com direções de fluxo subterrâneo. As determinações das radioatividades beta e alfa total foram realizadas a partir do emprego da infra-estrutura disponível no LABIDRO-Laboratório de Isótopos e Hidroquímica do Departamento de Petrologia e Metalogenia do Instituto de Geociências e Ciências Exatas da UNESP, grandemente implantada a partir de recursos fornecidos pela FAPESP e CNPq. Os sistemas foram calibrados para as determinações de interesse com traçador de atividade conhecida. Testes preliminares foram realizados em amostras de água de elevada radioatividade para se assegurar a aplicabilidade dos métodos. Concluiu-se que as águas analisadas possuem baixa radioatividade, tanto alfa quanto beta total, e, portanto, são adequadas para o consumo humano; que não há relação linear entre os dados obtidos e os dados químicos já disponíveis; e que a direção do fluxo subterrâneo do aqüífero não confere nenhuma tendência aos dados gerados.
Keywords: Águas subterrâneas; Radioatividade; Radioactivity